A complete asymptotic analysis of an oscillation free nonlinear equation of Bessel type with a pole in the dependent variable - Mingarelli, A.B.; Pacheco-Castelao, J.M.; Melkonian, S. (Нелінійні коливання, 2010)
We characterize the solution set of a nonlinear perturbation of Bessel’s equation of order zero on a half- line where the nonlinearity is analytic in the independent variable, algebraic in the dependent variable and, indeed, admits a pole in this variable. We show that the equation fails the Painleve´ test and that there are no points in [0,∞) where blow-up occurs. Although we cannot find even one closed-form solution, it is shown that there are only four families of solutions: those that are asymptotically linear and increasing, solutions that are asymptotically linear and decreasing, another set of solutions that are asymptotically constant, and a final set of solutions that admit singularities at finite points on [0,∞). As a consequence, we deduce that every solution with or without singularities on [0,∞) is non-oscillatory and, in fact, has at most two zeros. We also show that the plane Π of real initial conditions (y(0), y'(0)) can be decomposed into a union of connected regions, in each of which the solutions are exactly one of the types mentioned above. Furthermore, we obtain that the set of those initial conditions leading to asymptotically constant solutions is a piecewise differentiable curve in Π, one that can be estimated theoretically to a high degree of precision. In addition, the asymptotic behavior of solutions near a finite singularity is obtained. Esti- mates relating the growth of solutions to their initial conditions are also described and numerical examples are presented to illustrate the theory. Finally, we observe that every solution of our equation has finite si- ngularities when viewed as a solution on the whole line. Наведено опис множини розв’язкiв нелiнiйно збуреного рiвняння Бесселя нульового порядку на
пiвосi, де нелiнiйнiсть є аналiтичною вiдносно незалежної змiнної, алгебраїчною вiдносно залежної змiнної та фактично має полюс за цiєю змiнною. Показано, що рiвняння не задовольняє
ознаки Пейнлеве та не iснує точок на [0,∞), де розв’язок прямує до нескiнченностi. I хоча
не було знайдено розв’язку в явнiй формi, доведено, що iснують лише чотири сiм’ї розв’язкiв:
асимптотично лiнiйних та зростаючих, асимптотично лiнiйних та спадних, асимптотично
сталих та остання множина розв’язкiв, якi можуть мати особливостi в скiнченних точках
[0,∞). Як наслiдок встановлено, що кожний розв’язок, що має або не має особливостi, є неколивним i фактично має не бiльше двох нулiв. Також показано, що площину Π дiйсних початкових
умов (y(0), y'(0)) можна розбити на об’єднання зв’язних множин, в кожнiй з яких розв’язок належить однiй з описаних вище множин. Доведено, що множина початкових умов, якi приводять до
асимптотично сталих розв’язкiв, є кусково-диференцiйовною кривою в Π i може бути оцiнена з
високою точнiстю. Також описано асимптотичну поведiнку розв’язкiв в околi скiнченної особливостi. Отримано оцiнки зростання розв’язкiв в залежностi вiд початкових умов i наведено
числовi приклади, якi iлюструють теорiю. Насамкiнець показано, що кожен розв’язок рiвняння
має скiнченнi особливостi, якщо розглядати його на всiй прямiй.